Mentalizing in individuals with state and trait risk for psychosis: a systematic review - De Salve, Francesca; Rossi, Chiara; Oasi, Osmano (Frontiers in Psychiatry, 2023)
Background: Mentalization is an umbrella concept defined as the ability to interpret one's and others' mental states. Previous studies have hypothesized that mentalization may be a crucial resilience factor that significantly moderates the likelihood of developing psychotic disorders in individuals with both state and trait risk factors for the illness.The study reviews the role of mentalizing abilities (e.g., reflective functioning, Theory of Mind (ToM), and metacognition) in young adults with At-Risk Mental States (ARMS) and schizotypal traits. Specifically, the objective is to include articles that (a) evaluate the links between low mentalizing and both state (ARMS/CHR) and trait (schizotypy) risk for psychosis (b) compare the differences in mentalizing abilities between individuals with ARMS, schizotypy, full-blown psychosis, and healthy controls.Method: Electronic databases (PsycINFO, PubMed, Scopus, and Google Scholar) were used to search for articles, while Rayyan was employed to facilitate the screening and selection of studies. Eligible studies are original English-language; peer-reviewed research articles on populations that met validated risk diagnostic criteria for psychosis, ARMS, and healthy controls; empirical studies evaluating the association or differences between psychotic risk and mentalizing abilities. Non-English language studies, the ones not considering state or trait risk for psychosis, and qualitative studies were excluded. After the application of the PRISMA checklist and the inclusion and exclusion criteria previously mentioned, 10 articles were extracted. The systematic review has been registered on Prospero (CRD42023397594).Results: Low levels of reflective functioning and metacognition may predict a transition to psychosis. In addition, reflective functioning and metacognitive impairments are associated with attenuated This is a provisional file, not the final typeset article psychotic symptoms in both state risk groups and in non-clinical individuals with schizotypal traits. Concerning ToM tasks, mixed results emerged.The results obtained from the review suggest that the application of strategies to attenuate maladaptive metacognitive beliefs and low mentalization may be equally effective in improving psychotic symptoms. The assessment of mentalization and metacognition could potentially provide additional prognostic value over factors predisposing to psychosis. Good mentalization and metacognition functioning should be considered as protective factors able to minimize the transition to psychosis.